Analisis Perbandingan Aplikasi Akuntansi Berbasis Mobile Untuk UMKM - Vivka Guarda Putri; Dea Natasya Fahira; Arniati Arniati; Mega Mayasari (Journal of Applied Accounting and Taxation, 2023)
This study aims to provide recommendations for applications suitable for MSME. This study provides more detailed information about accounting-related mobile applications by analyzing application reviews independently through trials of mobile financial reporting applications. Also, it reviews users depending on ratings on Play Store or in the app store. The advantages and disadvantages of the application This is very critical to understand so that micro, small, and medium entrepreneurs can benefit. It is hoped that input will be obtained to develop MSMEs. This exploratory research uses a systematic method by looking for applications according to the keywords, for example, accounting applications, mobile applications, financial reports, and application recording finance, then grouping those apps by rating and the number of downloads to get some applications. The results of the study show that of the six applications reviewed based on independent reviews and user reviews, there are two main recommended applications: Cashbook: Cash Management App and Buku Warung Application for MSMEs. The reason behind the recommendation of these two mobile-friendly financial reporting applications is that the first. The Cashbook application: The cash Management App has advantages over other mobile-based financial reporting applications. This application is a multi-user application with reasonable access restrictions so that users of this application use the feature. Members do not need to worry about reporting errors. This advantage is why the Cashbook Application: Cash Management App is recommended for MSMEs who need structured and continuous recording without worrying about errors in the resulting reports. Furthermore, the Buku Warung Application for MSMEs is also a multi-user application that serves various alternative types of businesses as well as recording such as additional income features, including selling credit, electricity tokens, E-Wallet, data packages, Electricity Bills, BPJS, PDAM, Game Vouchers, Postpaid Credit, Credit Installments, and Internet and Cable TV. The QRIS facility has also been integrated with financial institutions. Thus, this increases the sense of security for application users in transactions.